Isothermal Pyrolysis of Bamboo and Pinewood Biomass: Product Characterization and Comparative Study in a Fluidized Bed Reactor - Manqoba Shezi; Sammy Lewis Kiambi (Bioengineering)
Fast pyrolysis of biomass is crucial for sustainable biofuel production, necessitating thorough characterization of feedstocks to optimize thermal conversion technologies. This study investigated the isothermal pyrolysis of bamboo and pinewood biomass in a sand-fluidized bed reactor, aiming to assess biomass suitability for commercial bio-oil production. The pyrolysis products and biomass species were characterized through proximate and ultimate analyses, along with GCMS, FTIR, SEM/EDX, and structural analysis to assess their chemical and physical properties. Results indicated that pine bio-oil possesses superior energy density, with a higher calorific value (20.38 MJ/kg) compared to bamboo (18.70 MJ/kg). Pine biomass yielded greater organic phase bio-oil (BOP) at 13 wt%, while bamboo produced 9 wt%. Energy yields were also notable, with pine exhibiting an energy yield of 15% for bio-oil organic phase (EBOP), compared to 11% for bamboo. The fibrous nature of bamboo biomass resulted in less-reacted biomass at constant reaction time due to flow resistance during pyrolysis. Pine bio-oil organic phase (P-BOP) demonstrated a higher heating value (23.90 MJ/kg) than bamboo (B-BOP). The findings suggest that while both biomass types are viable renewable energy sources, pine biomass is more favorable for commercialization due to its superior energy properties and efficiency in pyrolysis.